Desain Media Pembelajaran Bahasa Daerah Berbasis Aplikasi Digital untuk Mendukung Pelestarian Bahasa Lokal di Maluku pada Era Digital - Isabela xaveria (Community : Jurnal Pengabdian Pada Masyarakat, 2026)
The Hulung, Bobat, and Samasuru regional languages in Maluku are an important part of local cultural identity. Still, their existence is increasingly threatened by a decline in the number of speakers, particularly among the younger generation, and by the limited use of digital learning media. This community service activity aimed to design digital application-based regional language-learning media to support the preservation of local languages in the digital era. The service methods used are conceptual and descriptive, including a review of the current literature, a conceptual needs analysis of the target community, the design of digital learning media, and the evaluation of the outputs' suitability to the community's socio-cultural conditions. The results of the service activity are digital learning media that include vocabulary, everyday expressions, and local cultural content, designed to increase interest, awareness, and positive attitudes toward regional languages. This activity demonstrates that digital-based learning media has strategic potential for preserving local languages, although it still requires further development through field implementation and evaluation to achieve a real and sustainable impact on society.